The Relationship between Age and Pulp Cavity Size Using Cone-Beam Computed Tomography - Zahid, Hurraia; Nausheen, Neelofar; Nisar, Pashmina; Salam, Sobia; Ali, Asma; Siddique, Abu Bakar; Ullah, Irfan (Ibnosina Journal of Medicine and Biomedical Sciences, 2022)
Introduction This study aims to determine the relationship between chronological age and pulp cavity size and determine which type of tooth has a strong relationship between age and pulp cavity size.Materials and Methods Cone-beam computed tomography images from 200 patients aged between 18 and 55 years were analyzed. The software program (version 2.21) exported the images in the DICOM format, and the MIMICS software program (version 10.01) was used to calculate. The relationship between chronological age and pulp cavity size and determination of which type of tooth strongly relates to age and pulp cavity size were evaluated by Pearson correlation coefficient and Linear regression model.Results A total of 200 patients were included in the study. The minimum age recorded was 18 years, and the maximum period recorded was 55 years. The mean age was 35 years. The relationship between chronological age and pulp cavity size was statistically significant. Maxillary central incisor and mandibular first molar showed a strong relationship between chronological age and pulp cavity size.Conclusions In this study, the pulp cavity size of both maxillary central incisor and mandibular first molar showed a statistically significant correlation with age. The correlation between right and left is strong. So, maxillary central incisor and mandibular first molar is a valuable index for human age estimation with reasonable precision and accuracy.
Keywords: age estimation; cone-beam computed tomography; pulp cavity size; secondary dentin; radiation